Protective role of the mitochondrial fusion protein OPA1 in hypertension. Issue 7 (16th June 2021) - Robert, Pauline; Nguyen, Phuc Minh Chau; Richard, Alexis; Grenier, Céline; Chevrollier, Arnaud; Munier, Mathilde; Grimaud, Linda; Proux, Coralyne; Champin, Tristan; Lelièvre, Eric; Sarzi, Emmanuelle; Vessières, Emilie; et al.
Abstract: Hypertension is associated with excessive reactive oxygen species (ROS) production in vascular cells. Mitochondria undergo fusion and fission, a process playing a role in mitochondrial function. OPA1 is essential for mitochondrial fusion. Loss of OPA1 is associated with ROS production and cell dysfunction. We hypothesized that mitochondria fusion could reduce oxidative stress that defect in fusion would exacerbate hypertension. Using (a) Opa1 haploinsufficiency in isolated resistance arteries from Opa1 +/− mice, (b) primary vascular cells from Opa1 +/− mice, and (c) RNA interference experiments with siRNA against Opa1 in vascular cells, we investigated the role of mitochondria fusion in hypertension. In hypertension, Opa1 haploinsufficiency induced altered mitochondrial cristae structure both in vascular smooth muscle and endothelial cells but did not modify protein level of long and short forms of OPA1. In addition, we demonstrated an increase of mitochondrial ROS production, associated with a decrease of superoxide dismutase 1 protein expression. We also observed an increase of apoptosis in vascular cells and a decreased VSMCs proliferation. Blood pressure, vascular contractility, as well as endothelium‐dependent and ‐independent relaxation were similar in Opa1 +/−, WT, L‐NAME‐treated Opa1 +/− and WT mice. Nevertheless, chronic NO‐synthase inhibition with L‐NAME induced a greater hypertension in Opa1 +/− than in WT mice without compensatory arterial wall hypertrophy. This was associated with a stronger reduction in endothelium‐dependent relaxation due to excessive ROS production. Our results highlight the protective role of mitochondria fusion in the vasculature during hypertension by limiting mitochondria ROS production.